Mapping synaptic glutamate transporter dysfunction in vivo to regions surrounding Aβ plaques by iGluSnFR two-photon imaging - J. K. Hefendehl (Nature Portfolio, 2016)
In Alzheimer’s disease (AD), neural hyperactivity has been shown to occur in the regions surrounding Aβ plaques. Here, the authors use in vivotwo-photon imaging in mouse models of AD and report abnormal glutamate dynamics in the vicinity of plaques which can be partially restored via GLT-1 upregulation through Ceftriaxone treatment.